2023
DOI: 10.3390/ijerph20064925
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approach of Whole-Body Vibration Exercise on Wound Healing in Animal Models: A Systematic Review

Abstract: Human skin wounds pose a gathering threat to the public health, carrying an immense epidemiologic and financial burden. Pharmacological and non-pharmacological (NP) treatments have been proposed to the management of wound healing. Physical exercise is a strong NP intervention considered for patients in wound healing. Particularly, a type of exercise intervention known as whole-body vibration (WBV) exercise has gained increasing interest. WBV exercise is generated due to the transmission of mechanical vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…26 Employed for skeletal muscle training and increasingly in clinical settings, whole-body vibration (WBV) therapy has demonstrated numerous benefits 25 such as improved muscle strength, 27 increased bone mass, 28 better skin blood flow, 29 and reduced fat and blood glucose levels. 30,31 Extensively studied since the 1980s, 32 recent research, particularly in animal models, has highlighted its potential in wound healing [32][33][34][35] Studies have shown that WBV accelerates wound closure, re-epithelialization, and angiogenesis, especially in diabetic hard-to-heal animal models, by reducing tissue hypoxia and promoting tissue regeneration. [36][37][38][39] Notably, low-frequency and low-intensity WBV have been effective in improving both wound closure and healing quality, making it a promising therapeutic avenue for hard-to-heal wounds.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…26 Employed for skeletal muscle training and increasingly in clinical settings, whole-body vibration (WBV) therapy has demonstrated numerous benefits 25 such as improved muscle strength, 27 increased bone mass, 28 better skin blood flow, 29 and reduced fat and blood glucose levels. 30,31 Extensively studied since the 1980s, 32 recent research, particularly in animal models, has highlighted its potential in wound healing [32][33][34][35] Studies have shown that WBV accelerates wound closure, re-epithelialization, and angiogenesis, especially in diabetic hard-to-heal animal models, by reducing tissue hypoxia and promoting tissue regeneration. [36][37][38][39] Notably, low-frequency and low-intensity WBV have been effective in improving both wound closure and healing quality, making it a promising therapeutic avenue for hard-to-heal wounds.…”
Section: Introduction Backgroundmentioning
confidence: 99%